THE INFLUENCE OF QUALITY PRODUCT AND PRICE ON PURCHASE DECISION ON LINGKAR COFFEE - Farah Amalia; Bulan Prabawani; Dinalestari Purbawati (Jurnal Ilmu Administrasi Bisnis, 2025)
Abstract: This research aims to analyze the influence of product quality and price on consumer purchasing decisions for Kopi Lingkar products in Semarang City. Product quality and price are two factors that are often the main considerations for consumers when making a purchase. This research uses a quantitative method by distributing questionnaires to 100 respondents who have purchased Kopi Lingkar products. The data obtained was analyzed using PLS with two testing stages, namely Outer Model and Inner Model. The research type is explanatory research, nonprobability sampling type. The research results show that product quality has a positive and significant effect on purchasing decisions. price has a positive and significant effect on purchasing decisions, and product quality and price stimulantly have a positive and significant effect on purchasing decisions. Therefore, manufacturers are advised to continue to improve product quality and set competitive prices in order to attract consumer interest and increase sales. Keywords: Product Quality, Price, Purchase DecisionsTop of FormAbstraksi: Penelitian ini bertujuan untuk menganalisis pengaruh kualitas produk dan harga terhadap keputusan pembelian konsumen pada produk Kopi Lingkar di Kota Semarang. Kualitas produk dan harga merupakan dua faktor yang sering menjadi pertimbangan utama konsumen dalam melakukan pembelian. Penelitian ini menggunakan metode kuantitatif dengan menyebarkan kuesioner kepada 100 responden yang pernah membeli produk Kopi Lingkar. Data yang diperoleh dianalisis menggunakan PLS dengan dua tahap pengujian yaitu Outer Model dan Inner Model. Tipe penelitian adalah explanatory research tipe nonprobability sampling. Hasil penelitian menunjukkan bahwa kualitas produk berpengaruh positif dan signifikan terhadap keputusan pembelian. harga berpengaruh positif dan signifikan terhadap keputusan pembelian,dan kualitas produk dan harga secara stimulant berpengaruh positif dan signifikan terhadap keputusan pembelian,. Oleh karena itu, produsen disarankan untuk terus meningkatkan kualitas produk dan menetapkan harga yang kompetitif agar menarik minat konsumen dan meningkatkan penjualan.Kata Kunci: Kualitas Produk, Harga, Keputusan Pembelian